RANCANG BANGUN MESIN PENCACAH PLASTIK BERJENIS MULTILAYER DENGAN MODEL PISAU SHREDDER - Achmad Rafly Wardani (2023)
Garbage is leftover material that can have a negative impact on the environment and public health if it is not managed properly and correctly, one example is plastic waste. To reduce these negative impacts, plastic waste can be recycled into chopped plastic where the chopped results can be used as basic materials for further processing. The plastic shredder machine is designed to change the shape of plastic which was originally large in size to become smaller in the form of chopped pieces. The methods in this research are literature study, design process, manufacturing process, testing and formulation of results. The plastic shredder machine has dimensions of 680 mm in length, 500 mm in width and 1200 mm in height. This machine has several main components, namely the electric motor, gearbox, chain coupling, shredder knife, frame, in and outlet hopper. The machine has a prime mover, namely a 1 HP electric motor and engine rotation is channeled through a gearbox and chain coupling. The cost required in the machine manufacturing process is IDR 5,025,650.00 and the time required for the manufacturing process is 5.91 hours. The plastic shredder machine that has been made by the author has a chopping capacity of 10.29 kg/hour.